Validation of a Parvovirus B19 NAT Assay for Screening of Umbilical Cord Blood for Allogenic Hematopoietic Stem Cell Donation - Steininger, Philipp; Korn, Klaus; Hackstein, Holger; Strasser, Erwin F. (Transfusion Medicine and Hemotherapy, 2023)
Introduction: Parvovirus B19 transmitted by umbilical cord blood (UCB) products may cause severe disease in allogenic hematopoietic stem cell transplant recipients. Thus, commercially available nucleic acid test (NAT) assays for highly sensitive detection of parvovirus B19 DNA validated for the specimen cord blood plasma (CBP) are required to avoid parvovirus B19 transmission by umbilical hematopoietic stem cell preparations. Methods: The multiplex cobas DPX NAT assay was validated for detection of parvovirus B19 DNA in CBP derived from citrate anticoagulated UCB units which have been processed by the Rubinstein method. In total, 363 retained CBP samples pretested negative for parvovirus B19 DNA were prepared for analyzing sensitivity, specificity, and interference of that NAT assay. The 3rd WHO International Standard for parvovirus B19 DNA was used for determining the 95% limit of detection (LOD95) by probit analysis. Results: The validation of the parvovirus B19 NAT assay for CBP demonstrated high sensitivity, specificity, intra- and inter-assay precision. Dilution series and replicate analyses showed a high linearity of the assay with a coefficient of determination above 0.99 and revealed a LOD95 of 17 International Units (IU)/mL (95% confidence interval, 14-44 IU/mL) for parvovirus B19 DNA in CBP samples. Conclusion: The validation of a commercially available parvovirus B19 NAT assay for the specimen CBP demonstrated a high assay performance fulfilling German guidelines and international regulations.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Allogenic hematopoietic stem cell donation; Nucleic acid test screening; Parvovirus B19; Umbilical cord blood